2023
DOI: 10.3390/molecules28030970
|View full text |Cite
|
Sign up to set email alerts
|

DNA Base Excision Repair Intermediates Influence Duplex–Quadruplex Equilibrium

Abstract: Although genomic DNA is predominantly duplex under physiological conditions, particular sequence motifs can favor the formation of alternative secondary structures, including the G-quadruplex. These structures can exist within gene promoters, telomeric DNA, and regions of the genome frequently found altered in human cancers. DNA is also subject to hydrolytic and oxidative damage, and its local structure can influence the type of damage and its magnitude. Although the repair of endogenous DNA damage by the base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Therefore, if OGG1 does bind and subsequently resolve the G4 before cleaving the N-glycosyl bond, APE1 likely re-folds the G4 structure while bound. Moreover, prior work has shown that APE1 activity is greatly inhibited by G4 DNA despite tight binding affinities for the structure Sowers et al, 2023). Because pre-steady-state kinetics enable the resolution of distinct key catalytic steps (i.e., DNA cleavage and product release) and we utilized double-stranded AP-G4 VEGF promoter substrates, the work here expands on these prior observations.…”
Section: Ligation Depends On Fen1mentioning
confidence: 78%
“…Therefore, if OGG1 does bind and subsequently resolve the G4 before cleaving the N-glycosyl bond, APE1 likely re-folds the G4 structure while bound. Moreover, prior work has shown that APE1 activity is greatly inhibited by G4 DNA despite tight binding affinities for the structure Sowers et al, 2023). Because pre-steady-state kinetics enable the resolution of distinct key catalytic steps (i.e., DNA cleavage and product release) and we utilized double-stranded AP-G4 VEGF promoter substrates, the work here expands on these prior observations.…”
Section: Ligation Depends On Fen1mentioning
confidence: 78%
“…Therefore, if OGG1 does bind and subsequently resolve the G4 before cleaving the N‐glycosyl bond, APE1 likely re‐folds the G4 structure while bound. Moreover, prior work has shown that APE1 activity is greatly inhibited by G4 DNA despite tight binding affinities for the structure (Fleming et al, 2021; Sowers et al, 2023). Because pre‐steady‐state kinetics enable the resolution of distinct key catalytic steps (i.e., DNA cleavage and product release) and we utilized double‐stranded AP‐G4 VEGF promoter substrates, the work here expands on these prior observations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the C250 and C228 mutation hotspots in the hTERT promoter are not at CpG sites, and therefore 5 mC deamination and repair would not explain why these sites are mutational hotspots. While uracil repair within the hTERT promoter has not been investigated, it is known that the completion of DNA repair by the base excision-repair pathway can be inhibited when uracil bases are located within DNA sequences like telomeres that can form non-duplex structures [ 19 , 20 , 21 ]. Inefficient BER within the hTERT promoter could contribute to increased mutation frequencies.…”
Section: Introductionmentioning
confidence: 99%